The Effect Of Profitability And Leverage On Firm Value With Risk Management Disclosure As Moderating And Firm Size As Control - Shafaranti Wandira; Novita (Adpebi Science Series, 2024)
This research aims to determine investors' interest in investing by looking at the firm value. Some factors are profitability, leverage, risk management disclosure and company size. Data analysis uses a Multiple Regression Analysis model using SPSS 26 to produce a comprehensive view regarding interactions between variables. The sample used in this research consisted of 32 manufacturing companies in the pharmaceutical sector and food and beverage sector spanning the period 2020-2022 using a purposive sampling method for sampling. The research method used is quantitative. The data used is secondary data such as financial reports and annual reports. The research results show that profitability has a significant positive effect on company value, leverage and company size have no effect on company value. Risk management disclosure can moderate profitability and leverage on company value. The regression model shows that the influence of profitability and leverage on company value is only 22.5% and the remaining 77.5% is influenced by other things not included in the research.